Risk Assesment and Management Recommendations of Invasive Species in Papandayan Mountain Nature Reserve, West Java - Anggi Sella Nyuanti; Rina Ratnasih Irwanto; Elham Sumarga (3BIO: Journal of Biological Science, Technology and Management, 2020)
Natural disasters and anthropogenic disturbances have caused several locations in the Papandayan Mountain Nature Reserve to be more vulnerable and exposed further triggering the presence of invasive species. This presence impacts the environment, the economy, and the health of humans and animals. This research aims to assess the risks of these invasive species, followed by various recommendation strategies towards their species management. Data on species diversity was collected by vegetation analysis, using the quadratic method by purposively sampling plots. Results showed the existence of six invasive species in Papandayan i.e. Ageratina riparia (Regel) R.M.King & H.Rob., Ageratina adenophora (Spreng.) R.M.King & H.Rob.,Austroeupatorium inulaefolium (Kunth) R.M.King & H.Rob., Imperata cylindrica (L.) Raeusch., Rubus moluccanus L., and Ageratum conyzoides (L.) L.. The assessment of invasive species was assessed through two indices; Risk Index and Feasibility Index. Each of them was calculated based on the Risk Assessment Protocol to determine their strategy of control. Based on the Risk and Feasibility Indices, several recommendation strategies to manage invasive species are proposed.